2006
DOI: 10.1038/sj.bjc.6603438
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prognostic value of tumour cells detected by RT–PCR in peripheral blood stem cell collections from patients with Ewing tumour

Abstract: To retrospectively evaluate the incidence of tumour cell contamination of peripheral blood stem cell (PBSC) collections and to correlate these data with the clinical outcome after high-dose chemotherapy (HDCT) with stem cell rescue in patients with a highrisk Ewing tumour. Peripheral blood stem cell collections obtained from 171 patients were analysed. Tumour contamination was assessed by reverse transcriptase -polymerase chain reaction (RT -PCR). The files of 88 patients who underwent HDCT followed by PBSC re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 31 publications
(50 reference statements)
0
10
0
1
Order By: Relevance
“…These chimeric transcripts have been detected by reverse-transcriptase PCR (RT-PCR) for the diagnosis of ES. Due to the high sensitivity of the RT-PCR assay, it can also be used for detecting circulating tumor cells in peripheral blood (PBL) and bone marrow (BM) samples (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…These chimeric transcripts have been detected by reverse-transcriptase PCR (RT-PCR) for the diagnosis of ES. Due to the high sensitivity of the RT-PCR assay, it can also be used for detecting circulating tumor cells in peripheral blood (PBL) and bone marrow (BM) samples (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Retrospective analyses also indicated that RT-PCR positivity was associated with a greater risk for recurrence as well as distant metastasis (7,8). In studies where stem cell harvests were tested, a high percentage showed positivity by nested RT-PCR (9), although tumor cell contamination did not influence event-free or overall survival among high-risk EFT patients (10).…”
mentioning
confidence: 99%
“…However, only 11 publications of 147 (7.5%) emerged from paediatric cancer research, mostly on sarcomas [34][35][36][37][38][39][40][41][42][43][44].…”
Section: V) Connective Tissue Cancer Network (Conticanet) [33]mentioning
confidence: 99%